IL-6 and its role in IgA nephropathy development. (August 2022) - Groza, Yaroslava; Jemelkova, Jana; Kafkova, Leona Raskova; Maly, Petr; Raska, Milan
Abstract: IL-6 is considered one of the well characterized cytokines exhibiting homeostatic, pro- and anti-inflammatory activities, depending on the receptor variant and the induced intracellular cis- or trans-signaling responses. IL-6-activated pathways are involved in the regulation of cell proliferation, survival, differentiation, and cell metabolism changes. Deviations in IL-6 levels or abnormal response to IL-6 signaling are associated with several autoimmune diseases including IgA nephropathy (IgAN), one of most frequent primary glomerulonephritis worldwide. IgAN is associated with increased plasma concentration of IL-6 and increased plasma concentration of aberrantly galactosylated IgA1 immunoglobulin (Gd-IgA1). Gd-IgA1 is specifically recognized by autoantibodies, leading to the formation of circulating immune complexes (CIC) with nephritogenic potential, since CIC deposited in the glomerular mesangium induce mesangial cells proliferation and glomerular injury. Infection of the upper respiratory or digestive tract enhances IL-6 production and in IgAN patients is often followed by the macroscopic hematuria. This review recapitulates general aspects of IL-6 signaling and summarizes experimental evidences about IL-6 involvement in the etiopathogenesis of IgA nephropathy through the production of Gd-IgA1 and regulation of mesangial cell proliferation. Graphical Abstract: ga1 Highlights: IL-6 is involved in the etiopathogenesis of IgA nephropathy (IgAN). IL-6 enhances the production of IgA. IL-6 increases Galactose-deficiency in O -linked glycans attached to the hinge region of IgA1. IL-6 activate mesangial cells to proliferate and to produce IL-6. Urinary IL-6 level has a high predictive value in renal function outcome in IgAN.